PEMETAAN KOMPETENSI GURU MATA PELAJARAN EKONOMI TINGKAT SMA/SMK DI KABUPATEN TABALONG - Bachri, Achmad Alim (Vidya Karya, 2016)
Abstract: This research aimed to map the Economics teachers competence for vocational high school and senior high school level in Tabalong regency. This research was conducted through three strategic phases, namely (1) data collection, (2) analysis of data; and (3) the presentation of the results of data analysis (reporting) with the teachers as the research subjects. The data collection was conducted by survey method. The analysis of the data was carried out by descriptive quantitative and qualitative refering to Government Regulation No. 19 Year 2005 on National Education Standards and National Education Minister Regulation No. 16 of 2007 on Academic Qualification Standards and Teachers Competency. The research result shows that the teachers of high school education showed the good numbers in which all the core components that include pedagogical competence, personal competence, professional competence and social competence have been understood and implemented. It also occurs to vocational level students that indicates a high category for the average competence of teachers in the area of Economics either urban or peri urban typology. This condition illustrates that vocational school teachers performed in good numbers and it means that all the core components have been understood and implemented.Â Key words: mapping,Â Economics, teachersâ competence, Â Abtsrak: penelitian ini bertujuan untuk membuat pemetaan kompetensi guru bidang mata pelajaran Ekonomi tingkat SMA dan SMK di Kabupaten Tabalong. Penelitian dilakukan melalui tiga tahapan strategis, yaitu (1) pengumpulanÂ data, (2) analisis data; dan (3) penyajian hasil analisis data (pelaporan) dengan subyek para guru mata pelajaran ekonomi. Pengumpulan data dilakukan dengan metode survei. Data penelitian dianalisis menggunakan teknik deskriptif kuantitatif dan kualitatif dengan mengacu pada Peraturan Pemerintah No. 19 Tahun 2005 tentang Standar Nasional Pendidikan dan Peraturan Menteri Pendidikan Nasional No. 16 Tahun 2007 tentang Standar Kualifikasi Akademik dan Kompetensi Guru. Hasil penelitian menunjukkan bahwa tenaga pendidik satuan pendidikan SMA menunjukkan angka yang baik dimana seluruh komponen inti yang mencakup kompetensi pedagogik, kompetensi kepribadian, kompetensi profesional, dan kompetensi sosial telah dihayati dan dilaksanakan. Itu juga terjadi kepada tingkat SMK yang menunjukkan kategori tinggi untuk rata-rata kompetensi tenaga pendidik mata pelajaran Ekonomi baik pada wilayah tipologi urban maupun peri urban. Kondisi ini menggambarkan bahwa tenaga pendidik mata pelajaran Ekonomi SMK menunjukkan angka yang baik artinya seluruh komponen inti telah dihayati dan dilaksanakan.Â Kata kunci: pemetaan, mata pelajaran Ekonomi, kompetensi guru